Intensification of a distant hurricane by warm‐core eddies in the Gulf Stream in boreal fall - Keita Fujiwara; Ryuichi Kawamura (Atmospheric Science Letters, 2023)
Abstract This study investigated how warm‐core eddies (WCEs) in the Gulf Stream (GS) modulated the intensity of a distant tropical cyclone (TC) approaching the current in October. We performed cloud‐resolving regional simulations including a control run with the observed WCEs and a sensitivity run excluding the WCEs. These simulations found that the WCEs played a favorable role in the development of the distant TC. The WCEs affected the synoptic‐scale thermodynamic environments over the North Atlantic through the enhanced heat and moisture supply from the GS, increasing the moisture imports toward the distant TC. The WCEs‐enhanced moisture influx created very moist environments in the inner core. This inner‐core moistening was favorable for deep eyewall convection and an associated TC secondary circulation, leading to TC development. This result indicates the importance of WCEs in facilitating the remote process leading to TC development that previous studies have proposed.